Cast2Face: Character identification in movie with actor-character correspondence - XU, Mengdi (Institutional Knowledge at Singapore Management University, 2010)
We investigate the problem of automatically identifying characters in a movie with the supervision of actor-character name correspondence provided by the movie cast. Our proposed framework, namely Cast2Face, is featured by: (i) we restrict the names to assign within the set of character names in the cast; (ii) for each character, by using the corresponding actor's name as a key word, we retrieve from Google image search a group of face images to form the gallery set; and (iii) the probe face tracks in the movie are then identified as one of the actors by robust multi-task joint sparse representation and classification method. The assigned actor name on a face track is then mapped to the character name based on the cast again. In addition to face naming, we further apply the proposed method to spotlights summarization of a particular actor in his/her movies. Empirical evaluations on several feature-length movies demonstrate the satisfying performance of our method.